The association between aggressive and non-aggressive antisocial problems as measured with the Achenbach System of Empirically Based Assessment: A study of 27, 861 parent–adolescent dyads from 25 societies. (October 2015) - Burt, S. Alexandra; Rescorla, Leslie A.; Achenbach, Thomas M.; Ivanova, Masha Y.; Almqvist, Fredrik; Begovac, Ivan; Bilenberg, Niels; Bird, Hector; Chahed, Myriam; Dobrean, Anca; Döpfner, Manfred; Erol, Nese; et al.
Highlights: The association of aggression (AGG) with rule-breaking (RB) varies across samples. We found that the correlation was higher in boys, and varied by society. Parents' reports were more highly correlated than adolescents' self-reports. Their association was much lower when examining physical aggression per se. Abstract: Aggression (e.g., assaulting others, bullying, oppositionality; AGG) and non-aggressive rule-breaking (e.g., lying, stealing, vandalism; RB) appear to constitute meaningfully distinct dimensions of antisocial behavior. Despite these differences, it is equally clear that AGG and RB are moderately-to-strongly intercorrelated with one another. To date, however, we have little insight into the sampling and methodologic characteristics that might moderate the association between AGG and RB. The current study sought to evaluate several such moderators (i.e., age, sex, informant, and society) in a sample of 27, 861 parent–adolescent dyads from 25 societies. AGG and RB were assessed with the well-known Child Behavior Checklist and Youth Self-Report (Achenbach & Rescorla, 2001). Results revealed small effects of informant and adolescent sex, such that the association between AGG and RB was stronger for parents' reports than for adolescents' self-reports, and for boys than for girls. The association also varied by society. Unexpectedly, the specific operationalization of 'aggression' emerged as a particularly strong moderator, such that the association was stronger for a general measure of AGG than for a more focused measure of physical aggression per se. Such findings inform our understanding of similarities and differences between aggressive and non-aggressive antisocial problems.